DIRECTING HOUSEHOLD MONETARY SAVINGS TO INVESTMENTS IN UZBEKISTAN (European Journal of Economics, Finance and Business Development, 2025)
This article explores the potential of household monetary savings in Uzbekistan to serve as a key driver for domestic investment. Although household deposits in the country have significantly increased over recent years, the transformation of savings into productive investments remains low. Based on statistical data, household surveys, and international experiences, the study identifies key barriers such as low financial literacy, underdeveloped capital markets, and limited access to digital investment platforms. The paper presents a detailed analysis of savings and investment trends from 2019 to 2023 and suggests practical policy recommendations to mobilize household savings for long-term economic development. It concludes that expanding financial education, diversifying accessible investment instruments, and strengthening regulatory confidence are essential steps toward increasing household investment activity in Uzbekistan.